LATE DEVONIAN (FRASNIAN) CORALS FROM CENTRAL DOLPO, NEPAL (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
Rugosa and Tabulata from the Late Devonian of central Dolpo (Nepal) belong to the genera Kuangxiastraea, Scruttonia, Sinodisphyllum, Tabulophyllum (?), Fruehwirthia gen. n., Thamnopora, Cladopora, Alveolites and Alveolitella. The calcarenitic beds yielding the fossils are overlain by a prominent oolitic ironstone with thick ferruginous nodules and crusts. The age of the corals is probably Early Frasnian, thus younger than the Givetian fauna previously reported from eastern Dolpo. Biogeographic relations of the new fauna are with Western Europe and South China.
Keywords: Taxonomy; Paleobiogeography; Corals; Late Devonian; Himalaya; Nepal.